Vowel Insertion in Indonesian Phonology: A Generative Phonology Analysis with Phonetic Evidence - Naza Fanisa; Khanandya Nila Ulfah; Fajar Rahmatul Khalik; Dedy Suhery (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates vowel insertion in Indonesian by examining the phenomenon through both Generative Phonology and phonetic realization. The research is grounded in the framework of Chomsky and Halle (1968), who propose that phonological rules map underlying representations onto surface forms, and in Crystal’s (2008) description of epenthesis as the insertion of a sound to facilitate pronunciation. The data consist of Indonesian words containing illegal initial consonant clusters, alongside recordings from four native speakers whose pronunciations were analyzed auditorily. The generative phonology analysis reveals that vowel insertion functions as a systematic repair strategy triggered by clusters such as /st-/, /sp-/, /sk-/, and /sr-/, which violate Indonesian phonotactic constraints. The phonetic findings support this structure-driven analysis: all speakers consistently inserted a mid vowel—realized as [e] or [ə]—in the predicted environments, confirming the rule’s empirical validity. Taken together, the structural predictions and phonetic evidence demonstrate that Indonesian vowel insertion is both theoretically motivated and phonetically realized. The study contributes to the understanding of Indonesian phonology by showing how abstract phonological rules interact with actual speech production to maintain syllable well-formedness.